Kontribusi Resiliensi Akademik terhadap Subjective Well-Being pada Mahasiswa Akhir Program Studi Psikologi Universitas Negeri Padang - Anisa Resa Savitri (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Operationally, subjective well-being can be understood as an individual's assessment of their life experiences, involving affective components in the form of positive and negative emotions, as well as cognitive components. Individuals with subjective well-being experience more positive emotions and fewer negative emotions, and feel satisfied with their lives. One factor that influences subjective well-being is academic resilience. The purpose of this study was to determine the contribution of academic resilience to subjective well-being in final year psychology students at Padang State University. The research subjects were 174 final year psychology students at Padang State University who were taking thesis courses. The research design used was quantitative. Data collection used a non-probability sampling technique. Data were analyzed using simple regression analysis techniques. The analysis results obtained a sig. value of 0.000 (sig <0.05) with an r-square value of 0.550. From the results obtained, it was concluded that there was a contribution of academic resilience to subjective well-being in final year psychology students at Padang State University. The findings of this study strengthen the view that academic resilience is an important aspect in facing complex academic challenges, especially for final year students. Students with high levels of academic resilience tend to be better able to manage stress, maintain motivation, and remain focused on their academic goals despite facing various obstacles such as research difficulties, time pressure, and social demands. This ability directly contributes to increased life satisfaction and the dominance of positive emotions, which ultimately improves students' subjective well-being. Furthermore, the results of this study provide practical implications for universities to consider and develop programs that can improve students' academic resilience. For example, this could include providing counseling services, stress management skills training, and strengthening social support from supervisors and peers.